2017
DOI: 10.1638/2017-0098.1
|View full text |Cite
|
Sign up to set email alerts
|

DETECTION OF RANAVIRUS USING BONE MARROW HARVESTED FROM MORTALITY EVENTS IN EASTERN BOX TURTLES (TERRAPENE CAROLINA CAROLINA)

Abstract: The causes of free-living chelonian mortality events are often unknown because of infrequent recovery of remains and rapid postmortem decomposition. This study describes a technique to harvest bone marrow and detect frog virus 3-like ranavirus (FV3) using quantitative polymerase chain reaction in skeletonized eastern box turtles ( Terrapene carolina carolina) ( N = 87), and assesses agreement with concurrent perimortem samples ( N = 14). FV3 was detected in bone marrow samples from 12 turtle shells (14%). Thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Remains were completely skeletonized, precluding a definitive diagnosis. However, FV3 was not detected in banked shells, lowering the likelihood of one known cause of mass mortality [ 37 ]. Almost half of the live turtles were diagnosed with a necrotizing bacterial infection (NBI) based on histopathology (N = 2), consistent culture isolates (N = 4), and compatible clinical signs (N = 5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remains were completely skeletonized, precluding a definitive diagnosis. However, FV3 was not detected in banked shells, lowering the likelihood of one known cause of mass mortality [ 37 ]. Almost half of the live turtles were diagnosed with a necrotizing bacterial infection (NBI) based on histopathology (N = 2), consistent culture isolates (N = 4), and compatible clinical signs (N = 5).…”
Section: Discussionmentioning
confidence: 99%
“…DNA was isolated from oral swabs, whole blood, virus isolation flasks, bone marrow, and amphibian tissue samples using a commercially available kit (QIAmp DNA Blood Mini Kit and DNAeasy kit, Qiagen, Valencia, CA, USA). Manufacturer instructions were followed with some alterations for bone marrow samples, as previously described [ 37 ]. DNA concentration and purity was assessed spectrophotometrically (NanoDrop 1000, Thermo Fisher Scientific, Waltham, MA, USA) and DNA samples were stored at -80°C.…”
Section: Methodsmentioning
confidence: 99%
“…Using total IgY levels as an internal control may minimise diagnostic errors resulting from seasonal variations in antibody levels. PCR based assays have been used conventionally and in quantitative real-time assays to detect reptilian ranaviruses in a number of sample types including blood, oral and cloacal swabs, and fresh and fixed tissues (Pallister et al, 2007;Allender et al, 2013a;Goodman et al, 2013, Butkus et al, 2017Leung et al, 2017;Maclaine et al, 2018). Molecular surveys of turtle populations for ranavirus have revealed that swabs and blood samples are not equally valid targets for ranavirus detection (Allender et al, 2013a).…”
mentioning
confidence: 99%
“…both blood and swabs) when conducting a molecular survey for reptilian ranaviruses (a method employed in many studies). It is also possible to use bone marrow as a source of DNA for ranavirus detection from reptile carcases in which other viable tissue samples may have decayed (Butkus et al, 2017). The preferred target of ranaviral PCR assays is the major capsid protein (MCP) gene as it is highly conserved throughout the ranaviral lineage (Miller et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation